Atlantic ports and the first globalisation, c.1850-1930 - Suárez Bosa, Miguel (Cambridge imperial and post-colonial studies series., 2014)
Port cities were the means through which cultural and economic exchange took place between continental societies and the maritime world. In examining the ports of Brazil, the Caribbean and West Africa, this volume will provide fresh insight into the meaning of the 'First Globalisation'. Many of these ports were part of territories either governed or dominated by France, Britain, Spain or Portugal, that participated in global economy and society on very different terms from those northern European cities where major merchant and banking interests had their headquarters. Likewise, the ports of independent American countries underwent their own development processes. Taking the perspective of the Global South, the volume assesses this globalising trend, with its associated Industrial revolution, colonial expansion and new migrant and commodities flows. The international cast of authors in this collection bring fresh insight to this much debated period of history.